Why study the early Eucharist? - O'Loughlin, Thomas (University of Nottingham's Video Production Unit, 2013)
The Eucharist is a central element of the religious practice of the majority of Christians. Part of this practice is the act of recollection (anamnesis) of the origins of the practice which is located within memory at the salient moment of Jesus' last supper. However, this memory must be accompanied by study of the historical situation of its origins and early development in the early churches if some of the problems within the theology of the Eucharist are to be addressed adequately today.